ANALISIS PERBANDINGAN PAJAK PENGHASILAN YANG HARUS DIBAYAR SEBELUM DAN SESUDAH DITERAPKAN PP NO 46 TAHUN 2013 PADA PELAKU UMKM (Studi Kasus Pada Skala Bangun Perkasa CV) - Dwi Ulfa Sari; Naning Fatmawatie; Moh. Zuhri Fathoni (CAHAYA AKTIVA, 2018)
This research is conducted to know the comparison of Income Tax to be paid CV Skala Bangun Perkasa especially Toko Jaya Board in the year 2013-2016 both before and after applied Government Regulation No. 46 of 2013. The analysis used in this research is comparative descriptive analysis by elaborating the calculation process of Income Tax to be paid (indebted) CV Skala Bangun Perkasa based on Law No. 36 Year 2008 and then comparing with result of process of calculation of PP No. 46 Year 2013. Result of research this shows that the value of Corporate Income Tax to be paid CV Skala Bangun Perkasa 2013-2016 is smaller with the PP No. 46 of 2013 compared to the previous regulation is Law No. 36 Year 2008. In addition, the application of Government Regulation No. 46 of 2013 provides convenience in the calculation of Tax Income to be paid so that no tax consultant is required. With the simple calculation of Government Regulation No. 46 of 2013 can minimize the occurrence of errors in determining the amount of Income Tax to be paid. Keywords: Calculation of Corporate Income Tax, Law No. 36 Year 2008,PP No. 46 of 2013